2018
DOI: 10.1073/pnas.1719616115
|View full text |Cite
|
Sign up to set email alerts
|

Mid-level visual features underlie the high-level categorical organization of the ventral stream

Abstract: Human object-selective cortex shows a large-scale organization characterized by the high-level properties of both animacy and object size. To what extent are these neural responses explained by primitive perceptual features that distinguish animals from objects and big objects from small objects? To address this question, we used a texture synthesis algorithm to create a class of stimuli-texforms-which preserve some mid-level texture and form information from objects while rendering them unrecognizable. We fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
289
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(337 citation statements)
references
References 76 publications
23
289
1
Order By: Relevance
“…It is possible that these mid‐level properties also contribute to the patterns of response in category‐selective regions. Recently, images that preserve mid‐level properties of objects, but were not recognizable, elicited similar patterns of neural response to animacy and real‐world size found for intact objects (Long et al.,). When evaluating these possibilities, it is important to recognize that high‐level, mid‐level and low‐level contributions to the observed representational structure are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is possible that these mid‐level properties also contribute to the patterns of response in category‐selective regions. Recently, images that preserve mid‐level properties of objects, but were not recognizable, elicited similar patterns of neural response to animacy and real‐world size found for intact objects (Long et al.,). When evaluating these possibilities, it is important to recognize that high‐level, mid‐level and low‐level contributions to the observed representational structure are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 85%
“…Adaptation (different-same) changed very little across categories or image types. Colours reflect different subjects, with the group mean shown in black to animacy and real-world size found for intact objects (Long et al, 2018). When evaluating these possibilities, it is important to recognize that high-level, mid-level and low-level contributions to the observed representational structure are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pattern of response to each metameric object cluster was similar to the pattern of response elicited by the corresponding category-defined, object cluster. Given this, it is possible that other models that incorporate mid-level representations of objects may predict patterns of neural response more accurately than GIST (Guclu & van Gerven, 2015;Khaligh-Razavi & Kriegeskorte, 2014;Leeds, Seibert, Pyles, & Tarr, 2013;Long et al, 2018;Yamins et al, 2014). We found that the ability to find objects that had similar image properties to a category, but were not a member of that category varied for different categories.…”
Section: The Representation Of Objects Across Visual Cortexmentioning
confidence: 99%
“…Electrophysiological studies in nonhuman primates also suggest that the topography of higher visual areas is based on a continuous mapping of image features rather than discrete object representations (Tanaka, 1996). For example, categoryselective patterns of response are still evident when images have been scrambled in a way that preserves some of their visual properties, but removes their semantic properties (Andrews et al, 2010;Coggan, Liu, Baker, & Andrews, 2016;Long, Yu, & Konkle, 2018;Watson, Andrews, & Hartley, 2017). Neuroimaging studies have also shown that differences in the visual properties of objects can explain a significant amount of the variance in high-level regions of visual cortex (Coggan et al, 2019;Levy et al, 2001;Rice et al, 2014;Nasr et al, 2014;Sormaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%